A qualitative exploration of enablers for hepatitis B clinical management among ethnic Chinese in Australia. Issue 6 (18th March 2021) - Xiao, Yinzong; Wallace, Jack; Thompson, Alex; Hellard, Margaret; van Gemert, Caroline; Holmes, Jacinta A; Croagh, Catherine; Richmond, Jacqui; Papaluca, Tim; Hall, Samuel; Hong, Thai; Demediuk, Barbara; et al.
Abstract: An estimated 18% of people living with chronic hepatitis B (CHB) in Australia were born in China. While guideline‐based care, including regular clinical monitoring and timely treatment, prevent CHB‐related cirrhosis, cancer and deaths, over three‐quarters of people with CHB do not receive guideline‐based care in Australia. This qualitative study aimed to identify enablers to engagement in CHB clinical management among ethnic Chinese people attending specialist care. Participants self‐identified as of Chinese ethnicity and who attended specialist care for CHB clinical management were interviewed in Melbourne in 2019 (n = 30). Semi‐structured interviews covered experiences of diagnosis and engagement in clinical management services, and advice for people living with CHB. Interviews were recorded with consent; data were transcribed verbatim and thematically analysed. Receiving clear information about the availability of treatment and/or the necessity of long‐term clinical management were the main enablers for participants to engage in CHB clinical management. Additional enablers identified to maintain regular clinical monitoring included understanding CHB increases risks of cirrhosis and liver cancer, using viral load indicators to visualize disease status in patient‐doctor communication; expectations from family, peer group and medical professionals; use of a patient recall system; availability of interpreters or multilingual doctors; and largely subsidized healthcare services. In conclusion, to support people attending clinical management for CHB, a holistic response from community, healthcare providers and the public health sector is required. There are needs for public health programmes directed to communicate (i) CHB‐related complications; (ii) availability of effective and cheap treatment; and that (iii) long‐term engagement with clinical management and its benefits.